Proton-induced fixed positive charge at the Si(100)-SiO2 interface. - Godet, J; Giustino, F; Pasquarello, A (2007)
Positively charged defects induced by protons at the Si(100)-SiO2 interface are studied through density-functional calculations and realistic interface models. Protons generally preserve the bonding network, but cause the spontaneous breaking of strained bonds leading to threefold-coordinated Si(3)(+) and O(3)(+). Defect energies fall within a band of approximately 0.5 eV, which is stabilized by approximately 0.3 eV at the interface. Only the O(3)(+) at approximately 1 eV lower energies stand out as deep defects. This description is consistent with several experimental observations and supports the O(3)(+) as the origin of the fixed positive charge generated during silicon oxidation, in accord with a previous suggestion inferred from electrical data.